Simulations of the Early Holocene demise of the Laurentide Ice Sheet with BISICLES (public trunk r3298) ... - Matero, Ilkka; Gregoire, Lauren; Ivanovic, Ruza (UK Polar Data Centre, Natural Environment Research Council, UK Research & Innovation, 2019)
This dataset presents the input and output data from a set of sensitivity experiments to simulate the evolution of the Laurentide ice sheet in the Early Holocene (10-7 thousand years ago). These data are presented in the manuscript "Simulating the Early Holocene demise of the Laurentide Ice Sheet with BISICLES (public trunk revision 3298)". Simulating the demise of the Laurentide Ice Sheet covering the Hudson Bay in the early Holocene is important for understanding the role of accelerated changes in ice sheet topography and melt in the '8.2 ka event', a century long cooling of the Northern Hemisphere by several degrees. Freshwater released from the ice sheet through a surface mass balance instability (known as the saddle collapse) has been suggested as a major forcing for the 8.2 ka event, but the temporal evolution of this pulse has not been constrained. Dynamical ice loss and marine interactions could have significantly accelerated the ice sheet demise, but simulating such processes requires ... : The data is from a set of 11 simulations run with the BISICLES ice sheet model, setup to simulate the Laurentide ice sheet during the early Holocene period (10-7 ka). ...